Earthquake swarms in the Kamchatka-Commander Region - Zobin, Vyacheslav M.; Ivanova, Elena I. (Geophysical Journal International, 1994)
A swarm sequence is an earthquake sequence where no single event is dominant in size. In this paper we define a ‘swarm’ as an earthquake sequence where the energy difference between the largest shocks of the sequence is Δ K F ≤0.5 ( K F is an energy class of earthquake and represents an estimate of the energy of earthquakes in Log units of Joules for the frequency range 0.5–2.0 Hz. The relation between K F and magnitude MLH is K F = 0.85 MLH + 8.3. Magnitude MLH=1.3 M s −1.3 for the Kamchatkan earthquakes.) We analysed swarm sequences if they contained five or more events of the energy class K F ≥ 8.5 (MLH ≥ 1.0) occurring three days either side of the largest event (or, when more than one event happened with the same magnitude as the largest, the first of these)—termed a ‘clue’ event—and were located not further than 50 km from this clue event. These criteria allowed us to select 32 swarms with clue events of K F ≥ 11.5 (MLH ≥ 4.0) in the period 1962–1989 in the Kamchatka-Commander Region. the majority of swarms (86 per cent) were located within structures subject to horizontal tension (mainly on the slopes of the Aleutian and Kurile-Kamchatka trenches and in zones of modern volcanism). At the same time the appearance of earthquake swarms did not depend on the fault nature of the clue event in that swarm. We studied the relationships between the swarm characteristics (swarm area, duration and number of events) and the clue-event parameters (energy class, magnitude and stress drop). the regression equations were computed for parameters with significant correlation (at 95 per cent confidence level). All three swarm characteristics depend on the energy class of the clue-event. Magnitudes MLH are correlated with swarm area and duration. the clue-event stress drop gives a negative correlation with the number of events in a swarm.